2016
DOI: 10.3389/fpsyg.2016.00352
|View full text |Cite
|
Sign up to set email alerts
|

Walking in School-Aged Children in a Dual-Task Paradigm Is Related to Age But Not to Cognition, Motor Behavior, Injuries, or Psychosocial Functioning

Abstract: Age-dependent gait characteristics and associations with cognition, motor behavior, injuries, and psychosocial functioning were investigated in 138 typically developing children aged 6.7-13.2 years (M = 10.0 years). Gait velocity, normalized velocity, and variability were measured using the walkway system GAITRite without an additional task (single task) and while performing a motor or cognitive task (dual task). Assessment of children's cognition included tests for intelligence and executive functions; parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 67 publications
6
30
2
2
Order By: Relevance
“…This finding indicates that a concurrent motor task may cause greater dual-task gait decrements than a cognitive concurrent task what is in line with previous research (Cherng et al, 2007; Hagmann-von Arx et al, 2016) and may be interpreted from the perspective of the multiple-resource model of attention (Wickens, 1991). The model assumes that attentional resources are divided into various pools depending, for example, on the modality of input and response.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This finding indicates that a concurrent motor task may cause greater dual-task gait decrements than a cognitive concurrent task what is in line with previous research (Cherng et al, 2007; Hagmann-von Arx et al, 2016) and may be interpreted from the perspective of the multiple-resource model of attention (Wickens, 1991). The model assumes that attentional resources are divided into various pools depending, for example, on the modality of input and response.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, results showed that the difficult motor concurrent task led to greater gait alterations (i.e., greater decrease in stride length and greater increase in double limb support) compared to the cognitive concurrent tasks. In a similar vein, a recent study conducted by Hagmann-von Arx et al (2016) including school-aged children confirmed these findings by showing that gait performance was stronger affected in a motor dual-task condition in which children were asked to fasten and unfasten a shirt button than in a cognitive dual-task condition in which children were asked to listen to and memorize digits while walking.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations